PERBEDAAN RELIGIUSITAS DAN MOTIVASI BERPRESTASI PADA MAHASISWA UNIVERSITAS ISLAM NEGERI UIN MAULANA MALIK IBRAHIM MALANG - Susilawati, Samsul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
Religiosity is a religious appreciation and depth of trust expressed by daily worship, prayer, and reading of scripture. Religiosity can give a positive role to achievement motivation for the student. Correct understanding of his religion and the constant practice of his religious beliefs that will distinguish someone from others. Without a true understanding and practice of his religious beliefs, a necessity will form skilled individuals, initiative, leadership, responsible, honest, disciplined, loyal, optimistic, passionate and tolerant. Religious perspectives can play a positive role in relation to the achievement that the student will achieve in completing his education through understanding and belief in his religion. The higher the person's religious level the easier it will be for them to better complete their duties and responsibilities and to strive for difficulties in the face of religious values.Keywords: religiosity; achievement motivation